Enhanced electrocatalytic performance of NiOx@MnOx@graphene for oxygen reduction and evolution reactions. (11th October 2018) - Wang, Cheng Cheng; Yu, Zhan; Wang, Xin Tao; Lin, Bin
Abstract: Oxygen electrodes for oxygen evolution reaction and oxygen reduction reaction were intensively investigated due to high overpotential required to drive the four-electron process. A NiOx@MnOx@G nanostructure supported homogenously on graphene nanosheets through an easy and scalable self-assembly method was studied. The NiOx@MnOx@G exhibited a nanostructured NiO x nanocrystalline with size around 2.3 nm and an amorphous MnO x with controllable thickness. The 25% NiOx@MnOx@G showed remarkable activity for oxygen reduction reaction with a 4-electron process, the half-wave potential was 50 mV, but the stability of 25% NiOx@MnOx@G was better than Pt/C-JM. NiOx@MnOx@G nanostructure exhibited significantly better activity for oxygen evolution reaction compared with MnO x, which can demonstrate that NiO x could tune the activity of surface amorphous MnO x and dramatically increased oxygen evolution reaction activity. NiOx@MnOx@G is demonstrated with superior oxygen catalysts performance for reversible oxygen evolution and oxygen reduction reaction, due to the synergistic effect of NiO x and amorphous MnO x . Highlights: Bifunctional catalyst NiO x @MnO x /graphene was developed by self-assembly method. 25% NiO x @MnO x /graphene showed remarkable ORR and OER activity. Superior performance was due to synergistic effect of NiO x and MnOx.